Report on nutrition and small-scale irrigation - Feed the Future Innovation Lab for Small Scale Irrigation (Feed the Future Innovation Lab for Small Scale Irrigation, 2023)
The evidence on the potential for agricultural interventions to contribute to improved nutrition has grown considerably over the past decade. Numerous studies have explored both positive and negative effects of agriculture on nutrition and health. The Innovation Lab for Small Scale Irrigation has helped to fill the evidence gap on small-scale irrigation and nutrition linkages. The studies, implemented by the International Food Policy Research Institute and national partners, examine the potential of smallscale irrigation as a nutrition-sensitive investment. Through this work, more development partners are recognizing the interconnections and beginning to design irrigation investments to intentionally improve nutritional and health outcomes.